Scientific publication of psychology thesis advisors from 30 Peruvian universities [Publicación científica de asesores de tesis de psicología de 30 Universidades Peruanas] - Mamani Benito, Oscar Javier (2020)
ABSTRACT The objective was to determine the frequency of scientific publication of 231 psychology thesis advisors from 30 Peruvian universities, through a cross-sectional study. The results reveal that 58,4% have never published a scientific article; Only 26.8% have done so in the last three years and 18.2% in the last five years. 23.8% have managed to publish in journals indexed in SciELO and 14.7% in Scopus. In 10 of the 30 universities, more than 50% of the teachers had published a scientific article and only 2 to 5 universities had teachers who have published in the last 3 and 5 years. It is concluded that the scientific production of thesis advisors in psychology in Peru is low. This can have an impact on the generation of knowledge validated by the scientific community and, therefore, on the loss of opportunities for the development of a Peruvian psychology based on scientific evidence that meet the needs of the country.